Otimização da síntese de hidrogéis nanocompósitos intercalados para possível aplicação na área médica - Fernandes, Renan S. [UNESP]; De Moura, Marcia R. [UNESP]; Aouada, Fauze A. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2017)
In this study, the hydrogel formulations based on polysaccharide sodium alginate were investigated for further development of intercalated nanocomposite hydrogels, for purposes of future applications in the areas of health as a carrier in drug delivery systems. Thus, the objective of the work dealt with in the optimization of hydrogels synthesis and obtaining nanostructured hydrogels with clay in an intercalated conformation. The optimization of the hydrogel synthesis was successful, and it is possible to define the materials and / or solutions to be used and concentrations of these solutions to the best formulations of hydrogels. The choice of the concentration of the polysaccharide, the type of crosslinking agent and nanofiller to continued development work, it was determined following criteria as the degree of swelling, and in some cases the physical properties, contributed to determine the best hydrogels. The development of intercalated nanocomposites hydrogel beads was confirmed by the X-ray diffraction technique, which thus could be used to observe evidence of effective incorporation or intercalation of the nanoclay in the hydrogel matrix.
Optimization of synthesis of intercalated nanocomposite hidrogels for future application in the medical area
Keywords: Hydrogels; Intercalation; Nanocomposites; Nanofillers; Sodium alginate